Structural Variation within the Amygdala and Ventromedial Prefrontal Cortex Predicts Memory for Impressions in Older Adults - Cassidy, Brittany S.; Gutchess, Angela (Frontiers in Psychology, 2012)
Research has shown that lesions to regions involved in social and emotional cognition disrupt socioemotional processing and memory. We investigated how structural variation of regions involved in socioemotional memory [ventromedial prefrontal cortex (vmPFC), amygdala], as opposed to a region implicated in explicit memory (hippocampus), affected memory for impressions in young and older adults. Anatomical MRI scans for 15 young and 15 older adults were obtained and reconstructed to gather information about cortical thickness and subcortical volume. Young adults had greater amygdala and hippocampus volumes than old, and thicker left vmPFC than old, although right vmPFC thickness did not differ across the age groups. Participants formed behavior-based impressions and responded to interpersonally meaningful, social but interpersonally irrelevant, or non-social prompts, and completed a memory test. Results showed that greater left amygdala volume predicted enhanced overall memory for impressions in older but not younger adults. Increased right vmPFC thickness in older, but not younger, adults correlated with enhanced memory for impressions formed in the interpersonally meaningful context. Hippocampal volume was not predictive of social memory in young or older adults. These findings demonstrate the importance of structural variation in regions linked to socioemotional processing in the retention of impressions with age, and suggest that the amygdala and vmPFC play integral roles when encoding and retrieving social information.